Effects of an increase in Mexican strawberry exports to Canada on the profitability of pro-ducers in Mexico (Agro Productividad, 2023)
Objective: determine the viability of increasing the exported quantity of Mexican strawberries to the Canadian market.Design/methodology/approach: Likewise, a simulated scenario was developed with the purpose of carrying out a forecast on the conditions that may occur to have a more accurate knowledge of the operation of the international strawberry trade between Mexico and Canada. To perform this analysis, the international market was represented in a partial equilibrium model.Results: According to the calculated price flexibility, an increase in the exported quantity of Mexican strawberries to Canada of 50% in one year would cause a positive final effect. With this estimate, it can be established that an increase in the exported quantity of Mexican strawberries to Canada of 50% in one year would be viable in the economic sense. In this simulated scenario, the Benefit/Cost Ratio (B/C R) calculated for the producers of Michoacan, Baja California and Guanajuato would be 1.0865, 1.196 and 0.6856 respectively.Limitations on study/implications: not all products and all states of Mexico are examined.Findings/conclusions: The results showed that an increase in strawberry production to export to Canada in Michoacan and Baja California would be profitable for the producer, while an increase in strawberry production for export to the Canadian market in Guanajuato would further decrease profitability.